White Horse - Wurth, Erika T. (New York, NY : Flatiron Books, 2022)
When an old family bracelet inadvertently calls up both her mother's ghost and a monstrous entity, an urban indigenous woman searches for what happened to her mother all those years ago, forcing her to confront a long-denied truth and the one thing she's always wanted but could never have.
Keywords: Indians of North America -- Fiction; Family secrets -- Fiction; Monsters -- Fiction; Mothers and daughters -- Fiction; Denver (Colo.) -- Fiction; Paranormal fiction; Ghost stories; Horror fiction